The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/josi.12571
|View full text |Cite
|
Sign up to set email alerts
|

How stigma gets “in between”: Associations between changes in perceived stigma, closeness discrepancies, and relationship satisfaction among same‐sex couples

Abstract: Same-sex couples continue to experience social stigma, which can have negative consequences for the quality of their relationships. The current study combined minority stress theory with closeness discrepancy theory in an examination of how the production of disjunctures between actual and ideal experiences of closeness (i.e., closeness discrepancies) accounts for an indirect association between stigma and relationship quality. Data were obtained from a longitudinal study of same-sex couples in the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…Consistent with our hypotheses and expanding upon Frost and LeBlanc (2022) in this special issue, our quantitative analyses demonstrated that greater relationship stigma was associated with reduced relationship satisfaction, commitment, and increased closeness discrepancies, as well as with greater psychological distress. We also observed a partner effect or dyadic‐cross over effect whereby greater relationship stigma scores were associated with partners’ reports of lower relationship satisfaction.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with our hypotheses and expanding upon Frost and LeBlanc (2022) in this special issue, our quantitative analyses demonstrated that greater relationship stigma was associated with reduced relationship satisfaction, commitment, and increased closeness discrepancies, as well as with greater psychological distress. We also observed a partner effect or dyadic‐cross over effect whereby greater relationship stigma scores were associated with partners’ reports of lower relationship satisfaction.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, causal inferences are limited in the current study design such that it is plausible that indicators relationship quality and psychological distress may result in greater reports of relationship stigma. Thus, future research such as Frost and LeBlanc (2022) in this special issue that utilize longitudinal designs is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the research in this special issue, the role of policy in shaping relational outcomes for members of stigmatized groups has been highlighted. Eliminating discriminatory policy, such as marriage bans (Frost & LeBlanc, 2023), prohibitions on gender‐affirming care (Lewis et al., 2023), and forced relocation of people experiencing homelessness (Rea, 2023), as well as introducing policy aimed at remediating social inequalities, such as universal basic income (Petsnik & Vorauer, 2023), multicultural immigration policy (Froehlich et al, 2023), and adequate parental leave (Vink et al., 2023), will be vital to ensuring not only physical and mental health equity, but also equity in social health between members of stigmatized and dominant groups (Doyle & Link, 2022). It is our aim that this special issue points toward a framework for scholars to further push the boundaries in understanding the social consequences of stigma.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study found no evidence that mental illness disclosure facilitated reduction in prejudice, or that this was moderated by roommate closeness. Approaching closeness between relational partners from a slightly different angle, Frost and LeBlanc (2023) examined closeness discrepancies—that is, the extent to which one experiences a level of closeness that diverges from the level of closeness one desires, irrespective of whether this is higher or lower than actually experienced. The researchers proposed that closeness discrepancies can function as a mechanism linking experiences with stigma to impaired romantic relationship satisfaction among same‐sex couples.…”
Section: How Do Relationships Operate When Partners Are Faced With So...mentioning
confidence: 99%
“…At the same time, while the special issue generated a focus on social relationships it also allowed a broad consideration of many different stigmatizing circumstances. Relationship stigma is considered with respect to gender (Turetsky et al, 2023), low socioeconomic status (Park et al, 2023;Pestnik et al, 2023), mental illness (Ballinger et al, 2023) transgender people (Lewis et al, 2023) racism (Debrosse et al, 2023), same sex couples (Frost & Leblanc, 2023), weight (Schmidt et al, 2023), HIV (Gamarel et al, 2023;Khurshid et al, 2023), immigration status (Froehlich et al, 2023), gay men (Eschliman et al, 2023;Lattanner & Hatzenbuehler, 2023), homelessness (Rea, 2023), and women who earn more than their male partners (Vink et al, 2023). A final paper addressed 23 circumstances to show that mothers who experience stigma report more controlling behaviors with their daughters (Kazmierski et al, 2023. In addition to the breadth of conditions considered, the papers in the special issue span multiple levels.…”
Section: Situating This Special Issue Within the Context Of Prior Con...mentioning
confidence: 99%